Clinical data-mining in an allied health organisation : a real world experience - Giles, Roslyn; Epstein, Irwin; Vertigan, Anne (Sydney University Press, 2011)
'Clinical data mining in an allied health organisation: a real world experience' shows how data-mining methodology can be used to promote quality management and research in the work of allied health professions.